(untitled) (Web of Teachers: Inderscience Research, 2024)
This article addresses the challenges students face in developing speaking skills and explores the vital role of teachers play in overcoming these challenges. It identifies the hurdles students encounter, such as lack of confidence, limited practice opportunities, and public speaking anxiety. The text also explores strategies educators can use to help students improve, like creating a supportive environment, providing speaking chances, and giving constructive feedback. The importance of teachers in nurturing students’ speaking skills is stressed, emphasizing the need to guide, motivate, and involve students in various speaking activities. It also touches on how technology can aid both students and teachers in enhancing speaking skills. Overall, the article contributes to the discussion on student challenges in speaking skill development and underscores the crucial role of teachers play in addressing these obstacles.